2018
DOI: 10.1080/14737175.2018.1451329
|View full text |Cite
|
Sign up to set email alerts
|

Improving surgical outcome for gliomas with intraoperative mapping

Abstract: Radical glioma resection improves overall survival, both in low-grade and high-grade glial tumors. However, preservation of the quality of life is also crucial. Areas covered: Due to the diffuse feature of gliomas, which invade the central nervous system, and due to considerable variations of brain organization among patients, an individual cerebral mapping is mandatory to solve the classical dilemma between the oncological and functional issues. Because functional neuroimaging is not reliable enough, intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 98 publications
0
18
0
Order By: Relevance
“…From a neurosurgical perspective, it is mandatory to spare functional white matter tracts, which often constitute the functional boundary of resection identified with intraoperative mapping. 30 There is extensive literature to suggest that gliomas can change the diffusion profile of white matter tracts, as assessed on preoperative tractography. Several studies have reported that white matter microstructure can be affected by tumors.…”
Section: Discussionmentioning
confidence: 99%
“…From a neurosurgical perspective, it is mandatory to spare functional white matter tracts, which often constitute the functional boundary of resection identified with intraoperative mapping. 30 There is extensive literature to suggest that gliomas can change the diffusion profile of white matter tracts, as assessed on preoperative tractography. Several studies have reported that white matter microstructure can be affected by tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A MasSpec Pen was described adding to even better surgical removal of the tumor [ 34 ]. Awake surgery of the brain is yet another way to remove the tumor while sparing the healthy tissue [ 1 , 35 ]. However, awake surgery is not applicable to all patients due to anxiety and memories of the procedure [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, despite this major improvement of functional and oncological outcomes following LGG surgery in the two past decades (11), because of its intrinsic diffuse nature, LGG cannot be cured, as evidenced by relapse that may arise even many years after supratotal resection (4). As a consequence, reoperation(s) has been advocated in the event of LGG recurrence, with the aim of reducing again the tumor volume and then decreasing the risk of malignant transformation and prolonging overall survival (12, 13).…”
Section: Surgery For Low-grade Glioma and Functional Rearrangementmentioning
confidence: 99%